Numerical Activities of Daily Living – Financial (NADL-F): A tool for the assessment of financial capacities‡. Issue 7 (9th August 2019) - Arcara, Giorgio; Burgio, Francesca; Benavides-Varela, Silvia; Toffano, Roberta; Gindri, Patrizia; Tonini, Elisabetta; Meneghello, Francesca; Semenza, Carlo
ABSTRACT: Financial capacity is the ability to manage one's own finances according to self-interests. Failure in financial decisions and lack of independence when dealing with money can affect people's quality of life and are associated with neuropsychological deficits or clinical conditions such as mild cognitive impairment or Alzheimer's disease. Despite the importance of evaluating financial capacity in the assessment of patients with neuropsychological and psychiatric disorders, only a few tools have been developed. In the present article, the authors introduce the Numerical Activities of Daily Living – Financial (NADL-F) test, a new test to assess financial capacity in clinical populations. The NADL-F is relatively short, yet it encompasses the most common activities involving financial capacities. The NADL-F proved to have satisfactory psychometric properties and overall good validity for measuring financial abilities. Associations with performance on basic neuropsychological tests were investigated, in particular focusing on mathematical abilities as cognitive correlates of financial capacity. Results indicate that the NADL-F could be a useful tool to guide treatments for the enhancement of financial capacities. By sharing all materials and procedures, the authors hope to promote the development of further versions of the NADL-F in different languages, taking into account the necessary adjustments related to different socio-cultural contexts.